SharePoint 2010 as a Development Platform - Krause, Joerg; Dring, Martin; Langhirt, Christian; Pehlke, Bernd; Sterff, Alexander; Krause, Andrew (Apress : Imprint: Apress, 2010)
SharePoint is gaining recognition as a full-fledged application server with many features and enhancements that specifically allow non-developers to create sophisticated intranet sites. However, with the 2010 release, Microsoft's SharePoint increasingly becomes a compelling development platform. The strong application programming interface (API), its highly extensible nature, and its foundation on the underlying .NET Framework all generate "the perfect storm" to make it one of the most powerful web development platforms available. However, with power comes complexity. The wide range of usage scenarios make it difficult for developers to grasp the full ability of this next-generation platform. This book takes an in-depth, all-encompassing approach to programming concepts, the extensibility interfaces, and how to embrace SharePoint as a toolkit full of features available to web developers. Take an in-depth look into the internals of SharePoint. Create sophisticated applications using SharePoint controls and databases. Understand the API and use in conjunction with ASP.NET to extend SharePoint. SharePoint is more than a portal and more than an intranet. Harness its capabilities and put it to work for you.